Form from form : poems - Bolin, Christopher (University of Iowa Press, 2018)
"Was it a crater or a sinkhole?" asks a voice in one of the mysterious, wonderstruck poems in Christopher Bolin's Form from Form, whose cadences modulate with the energies of form-making, deformation, and elusive reformation. Natural forms and forms of human manufacture, forms of absence and those of urgent desire construct and deconstruct each other in Bolin's singular music, which blends unnerving plainness and obliqueness, the childlike and the alien. As their sites drift from workers' camps to city squares, isolated coasts to windswept plains, the poems in Form from Form trace a map of a fragmented ecology, dense with physical detail of altered landscapes and displaced populations. In tones of austere beauty and harsh discordance, these poems provide a "field guide to luminescent things," a visionary fretwork of the possibilities and impossibilities of faith in the present moment
Keywords: American poetry.; Poésie américaine.; FICTION -- General.; POETRY -- General.; American poetry